Comparison of Botanical Characteristics of 4 Cultivars of Nelumbo nucifera Gaertn. for Utilization - Noimai, Yaowamal; Dechsungnoen, Rujira; Kladdang, Kritsanah (Journal of Applied Research on Science and Technology (JARST), 2021)
This study was aimed to compare the botanical characteristics of four Lotus cultivars. The experiment was conducted by completely randomized design (CRD). Lotus were planted 10 replications in 50 x 50 cm pot size and repeated 3 bio-replication. This study was done form June to November 2018 at the Lotus and Waterlily Museum of Rajamangala University of Technology Thanyaburi. The qualitative of the botanical characters for utilization; No. of leaf, petiole, peduncle, flower, petal, stamen, pistil, torus, seed and rhizome were study and compared between the differences four lotus cultivars. N. nucifera ‘Pathum’ cultivars showed the fastest growing and the best flower production (16 flowers per plant) that suitable for cut flowers utilization. N. nucifera ‘Nakhonsawan’ showed the highest seeds production (84.11%), following by N. nucifera ‘Pattama ubon’ (75.29%) and the N. nucifera ‘Rachinee’ (67.96%) respectively. N. nucifera ‘Rachinee’ showed the highest root (rhizome) production (885.17 grams per plant), following by N. nucifera ‘Pattama ubon’ (585 grams per plant) and N. nucifera ‘Nakhonsawan’ (430.67 grams per plant) respectively. The average in each parameter was statistically significant differences (p ≤ 0.05) when compared by the Duncan’s New Multiple Range Test (DMRT). The results revealed that the capacity to select the suitable lotus cultivar for utilization lotus improvement in the future.